2018
DOI: 10.1016/j.jqsrt.2017.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Polarized scattering by Gaussian random particles under radiative torques

Abstract: We study the internal alignment of a statistical ensemble of Gaussian random ellipsoids with respect to the radiation direction. We solve the rigid body dynamics due to scattering forces and torques, using a numerically exact and efficient T-matrix solver for arbitrary particle shapes and compositions. We then compare the polarization of the aligned ensemble to a randomly oriented ensemble and a perfectly aligned ensemble. We find that the ensemble becomes partially aligned under monochromatic radiation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…where u rad , λ, and a eff are the radiation energy density, wavelength and the equivalent volume sphere radius of the scatterer. Herranen et al (2018) showed via explicit integration that RATs rapidly cause stable angular speeds in interstellar-like conditions. When interstellar conditions, specifically the radiation intensity, are translated to correspond the circumsolar environment, the timescales of reaching stability are of seconds, corresponding to the million-fold increase in radiation density.…”
Section: Spin-up By Radiative Torquesmentioning
confidence: 99%
“…where u rad , λ, and a eff are the radiation energy density, wavelength and the equivalent volume sphere radius of the scatterer. Herranen et al (2018) showed via explicit integration that RATs rapidly cause stable angular speeds in interstellar-like conditions. When interstellar conditions, specifically the radiation intensity, are translated to correspond the circumsolar environment, the timescales of reaching stability are of seconds, corresponding to the million-fold increase in radiation density.…”
Section: Spin-up By Radiative Torquesmentioning
confidence: 99%
“…In previous studies [7,8] we have combined into a single software framework a T-matrix [9] scattering solution for particles of arbitrary shape and composition with an integrator of the equations of motion of the particle. This dynamical response by electromagnetic interactions is hereafter called scattering dynamics.…”
Section: Introductionmentioning
confidence: 99%